2014
DOI: 10.17219/acem/37214
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Dexmedetomidine vs. Ketamine in Cardiac Ischemia/Reperfusion Injury in Rats – Preliminary Study

Abstract: Objectives. Following ischemia/reperfusion injury, antioxidant defense mechanisms may remain insufficient depending on the duration of ischemia which is caused by any reason (MI, after percutaneous coronary intervention, during cardiac surgery). After that, free oxygen radicals increasing within the cell cause structural deterioration. Cytokines which activate a series of reactions that cause tissue damage and inflammatory response are released during reperfusion of ischemic tissues. In this study, we aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…It has been reported that LRIP effectively reduces the ischemic injury of the brain [34], heart [35], or other organs [36] in experimental and clinical research. Many anesthetics are reported to be able to reduce the ischemic brain injury by offering neuroprotection through anti-inflammatory [6] or anti-apoptotic/anti-cell death effects [8]. Apart from that, a growing body of preclinical literature also implicates anesthetic agents such as barbiturates, volatile anesthetics, propofol, and isoflurane in exhibiting neuroprotective properties in various preclinical studies [37,38].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that LRIP effectively reduces the ischemic injury of the brain [34], heart [35], or other organs [36] in experimental and clinical research. Many anesthetics are reported to be able to reduce the ischemic brain injury by offering neuroprotection through anti-inflammatory [6] or anti-apoptotic/anti-cell death effects [8]. Apart from that, a growing body of preclinical literature also implicates anesthetic agents such as barbiturates, volatile anesthetics, propofol, and isoflurane in exhibiting neuroprotective properties in various preclinical studies [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the common anesthetics used during MCAO include chloral hydrate, isoflurane, sevoflurane, ketamine, and ketamine-xylazine [3][4][5]. These anesthetics have also been documented to have some anti-inflammatory [6,7] and anti-apoptotic properties [8], which may protect the brain from stroke pathology. Ketamine and halothane are also widely used anesthetics for many surgical procedures in animal models [9], and conflicting results have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is also one of the important mechanisms of cardiac toxicity induced by Doxorubicin [33, 34]. GSH-PX was able to catalyze reduction reaction of reduced glutathione with hydrogen peroxide specifically, and remove harmful peroxide metabolites timely, thereby block a series of lipid peroxidation and protect structure and function of cell completely [35]. The activity of SOD indirectly reflects the ability of removing oxygen free radicals [36].…”
Section: Discussionmentioning
confidence: 99%